Human Capital Investment and Globalization in Extortionary States - Fredrik Andersson; Kai A. Konrad (Institute for the Study of Labor (IZA), 2001)
This paper considers education investment and public education subsidies in closed and open economies with an extortionary government. The extortionary government in a closed economy has incentives to subsidize education in order to overcome a hold-up problem of time consistent taxation, similar to benevolent governments. The two types of government differ in their education policies if highly productive labor is fully mobile. Extortionary governments? incentives for education subsidies vanish and they even have an incentive to prevent individuals from mobility increasing education investment. Tax competition therefore reduces hold-up problems of time consistent extortionary taxation, but also introduces incentives that reduce workers? utility.
Keywords: H21; H23; 330; Globalization; commitment; time consistent income taxation; migration; education; Bildungsinvestition; Einkommensteuerpolitik; Bildungspolitik; Internationale Arbeitsmobilität; Steuerwettbewerb; Leviathan-Modell; Öffentliche Bildungsausgaben; Globalisierung; Theorie